Analysis Relationship between Free Fatty Acid and Peroxide Values in Crude Palm Oil Industry - Ramlan Silaban; Marta Adeliana Sijabat; Afrilita Harahap; Timotius Agung Soripada; Marham Sitorus; Eddiyanto; Ahmad Nasir Pulungan (SCIENCE AND TECHNOLOGY FACULTY OF UNIVERSITAS ISLAM NEGERI RADEN FATAH PALEMBANG, 2026)
Crude Palm Oil (CPO) is crude palm oil extracted from the palm oil industry that has not undergone a refining process. CPO quality is considered good if it meets applicable quality standards. This study aims to determine a mathematical equation model that describes the relationship between free fatty acid value (FFA) quality parameters and peroxide value (PV) in CPO samples. FFA content analysis was carried out using the alkalimetric titration method, while the peroxide value was tested using the iodometric titration method. The storage time variations used were 0 - 3 weeks. The results showed that : (1). The sample consist Free Fatty Acid value (FFAV) were 2.97%; 3.22%; 3.41%; and 3.66%, respectively, with an average of 3.31%. Meanwhile, Peroxyde Value (PV) ​​were obtained at 1.85; 2.25; 2.65; and 3.04 meq O₂/kg. (2). According to these results, the FFAV content still meets the Indonesian National Standard (SNI) standard (<5.0%) and the PV value is also below the SNI limit (<10 meq O₂/kg). (3). The mathematicals model of relationship between FFAV shows a significant effect with a linear regression equation of Y = 0.436x + 0.0221 and a determination value (R²) of 0.0976. (4). This model indicates that an increase in FFA levels is directly proportional to an increase in peroxide value. The mathematical model obtained illustrates that an increase in PV is in line with an increase in FFA levels, both of which play an important role in determining the quality stability and storage durability of CPO.